Treatment of PCL, ACL, and Lateral-Side Knee Injuries: Acute and Chronic - Levy, Bruce A.; Stuart, Michael J. (The Journal of Knee Surgery, 2012)
Combined posterior cruciate ligament, anterior cruciate ligament, and lateral-side disruption is one of the more common patterns of multiligament knee injury. This is a devastating injury with significant long-term functional sequelae, making accurate diagnosis and management extremely important. While surgical intervention is necessary to restore function, the specific management strategies remain controversial. This article will review the current literature and the authors' preferred approach including physical examination, imaging, timing of surgery, surgical technique, and postoperative rehabilitation.
Keywords: knee dislocation; multiligament knee injury; posterolateral instability; fibular collateral ligament reconstruction